2021
DOI: 10.3390/foods10122980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Essential Oils and Vacuum Packaging on Spoilage-Causing Microorganisms of Marinated Camel Meat during Storage

Abstract: The use of essential oils (EOs) and/or vacuum packaging (VP) with meats could increase product shelf-life. However, no studies investigating the effect of EOs and VP on camel meat background microbiota have been conducted previously. The study aimed to analyze the antimicrobial effect of essential oils (EOs) carvacrol (CA), cinnamaldehyde (CI), and thymol (TH) at 1 or 2% plus vacuum packaging (VP) on the growth of spoilage-causing microorganisms in marinated camel meat chunks during storage at 4 and 10 °C. VP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
(55 reference statements)
3
15
1
Order By: Relevance
“…Microbial analyses were performed as per previously published protocols (FDA, 2015; Osaili, Hasan, Al‐Nabulsi, Dhanasekaran, Obaid, Hashim, et al., 2021). Samples were analyzed on days 0, 1, 4, and 7.…”
Section: Methodsmentioning
confidence: 99%
“…Microbial analyses were performed as per previously published protocols (FDA, 2015; Osaili, Hasan, Al‐Nabulsi, Dhanasekaran, Obaid, Hashim, et al., 2021). Samples were analyzed on days 0, 1, 4, and 7.…”
Section: Methodsmentioning
confidence: 99%
“…Some features to consider for proper processing and storage are high water activity (aw), pH, and nutrient content. Together, these elements create an excellent medium for the proliferation of microorganisms [ 14 ]. The most common problems with spoilage in meat and meat products result from the ease with which they are affected by high rates of lipid oxidation and microbial contamination if they are not correctly handled and/or preserved.…”
Section: Mechanism Of Deterioration In Meatmentioning
confidence: 99%
“…Because it is a raw material, meat is susceptible to quality deterioration during processing, especially if mishandled. In addition, the high water-activity characteristic of meat (~0.99) makes it an excellent medium for microorganism proliferation [ 14 , 27 ]. Common pathogens in meat include Campylobacter jejuni , Clostridium perfingens , Escherichia coli O157:H7, Listeria monocytogenes , Salmonella , Staphylococcus aureus , and Campylobacter spp.…”
Section: Mechanism Of Deterioration In Meatmentioning
confidence: 99%
“…In addition, it provides water retention and product yield (ALAHAKOON et al, 2014). Thus, it improves the microbiological quality of the product and increases its shelf life (BALTIĆ et al, 2015;KARAM et al, 2020;OSAILI et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Spice extracts such as oregano, rosemary, coriander, thyme and basil, among others, may be potential natural antioxidants in meat products (FELLENBERG et al, 2020). In addition, they are inhibitors of food-borne microorganisms due to the presence of phenolic compounds in their composition (BOSKOVIC et al 2017;STANOJEVIC et al, 2017;BOSKOVIC et al, 2019;KARAM et al, 2020;OSAILI et al, 2021). Furthermore, studies have shown the influence of the use of natural additives on the color (MILANI et al, 2010) and flavor of meat products (BOSKOVIC et al, 2019).…”
Section: Introductionmentioning
confidence: 99%